2012
DOI: 10.1111/j.1875-595x.2011.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile telephone short message service as a reminder: the effect on patient attendance

Abstract: The study results indicate that sending appointment reminders as text messages to patients is an effective strategy to reduce nonattendance rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 7 publications
4
51
0
Order By: Relevance
“…In contrast, for cancellations, the authors found that the rate continues to rise with time interval up to and beyond 1 month. A study of adult primary care in Geneva 79 reported that having a follow-up appointment of more than 1 year was significantly associated with missed appointments. Similarly, an Australian study in a general hospital setting 93 reported that those with a waiting time of more than 21 days until their appointment were significantly less likely to attend than those with a shorter waiting time (OR 2.8; p = 0.002).…”
Section: Time To Wait To the Appointmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, for cancellations, the authors found that the rate continues to rise with time interval up to and beyond 1 month. A study of adult primary care in Geneva 79 reported that having a follow-up appointment of more than 1 year was significantly associated with missed appointments. Similarly, an Australian study in a general hospital setting 93 reported that those with a waiting time of more than 21 days until their appointment were significantly less likely to attend than those with a shorter waiting time (OR 2.8; p = 0.002).…”
Section: Time To Wait To the Appointmentmentioning
confidence: 99%
“…Those who were disturbed by the reminder gave the following reasons: telephone call too early in the morning, they were waiting for other important results, they were contacted at work, felt that were being treated as senile or felt that the reminder was unnecessary. 79 …”
Section: Patterns and Influences On Health-care Attendance Behaviourmentioning
confidence: 99%
See 3 more Smart Citations